Pertanggungjawaban Komando Militer Dalam Kejahatan Perang - Muhammad Aryo Dwinanda Mukti; Irwan Triadi (Jurnal Relasi Publik, 2024)
It is customary in the military world that unit commanders are responsible for the actions taken by their subordinates in carrying out their duties. This also includes violations occurring in war. This research uses a normative juridical research type with library study data collection techniques. The approach used in this research is a statutory approach and a conceptual approach. The result of this research is that not all subordinate mistakes can be included in command responsibility which is also borne by the superior or unit commander. This is because command accountability must at least fulfill several elements which include, the existence of a superior and subordinate relationship, the superior's knowledge of crimes committed by his subordinates, and the existence of failure to act, namely action that fails to be taken to prevent, punish and stop criminal acts committed by his subordinates.